Pengembangan Kurikulum Diklat Teknis Pengelolaan Barang Milik Daerah Berbasis Kompetensi Pegawai - Djadjat Sudrajat (Lembaga Administrasi Negara, 2020)
The low competency of employees in the management of regional property in the West Java Provincial Government is a challenge for the West Java Province's Human Resource Development Agency (BPSDM) in developing apparatus competencies through education and training. The research aims to find out how much influence the policy instruments (policy instrument) and policy implementation (policy implementation) have in developing employee competencies through the technical training curriculum for regional property management. This study uses descriptive analysis with a qualitative approach. The data was explored in the form of the implementation of the technical training curriculum for the management of regional property held at the Human Resources Development Agency (BPSDM) of West Java Province in 2018. Data and information collection methods were carried out through observation, interviews, and document review. The results of the study show that there were errors in policy instruments (policy instruments) and policy implementation in determining the technical training curriculum for the management of regional property. Policy instruments through the establishment of curriculum (learning objectives, training courses, media and learning methods) and policy implementation through the implementation of curriculum (teaching and learning process and assessment) have not been oriented to competency requirements in accordance with training competency/employee position standards. competency of education and training graduates is not optimal.Keywords: Development of competency-based, profesional, competency-based curriculum